Personality and older consumers' green behaviour in the UK. (August 2015) - Gordon-Wilson, Sianne; Modi, Pratik
Highlights: We look at how older consumers' personality type explains their green behaviour. The openness personality trait is positively linked to their green behaviour. The extraversion personality trait is negatively related to their green behaviour. The level of green behaviour increased with older consumers' age but this did not reach significance. There is a need to educate older consumers about adopting more green behaviour. Abstract: The UK government has set an ambitious target of reducing greenhouse gas emissions by 80% before 2050. An interesting segment that could help to achieve this is older consumers, due to their growing numbers. There seems to be a lack of attention, in the research looking specifically at different age categories of older consumers' green behaviour, and whether their level of greenness can be explained by their personality. Using Socioemotional Selectivity Theory and Time Perspective, the research presented here was designed to provide an exploratory analysis of how the green behaviour of older consumers is explained by their personality types. Based on the responses of 204 older consumers in the UK, our results find the openness personality trait to be positively linked to green behaviour, whilst the extraversion personality trait is negatively related to green behaviour. Although the level of green behaviour increased with older consumers' age, this did not reach significance.